2019
DOI: 10.1161/jaha.119.014906
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Site Variation in High‐Risk Coronary Intervention and the Use of Mechanical Circulatory Support: Insights From the Veterans Affairs Clinical Assessment Reporting and Tracking (CART) Program

Abstract: Background Patients undergoing percutaneous coronary intervention ( PCI ) are older with greater medical comorbidities and anatomical complexity than ever before, resulting in an increased frequency of nonemergent high‐risk PCI ( HR ‐ PCI ). We thus sought to evaluate the temporal trends in performance of HR ‐ PCI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 39,40 Heart team management decisions should also weigh the relative risks and benefits of both MCS‐assisted and unassisted PCI compared with available surgical therapeutic options including surgical revascularization, durable LV assist device implantation, and heart transplantation. Appropriate patient selection is particularly critical in light of the potential for device‐related complications 44‐46 …”
Section: Preprocedural Assessment Of Coronary Anatomical Complexity Amentioning
confidence: 99%
“… 39,40 Heart team management decisions should also weigh the relative risks and benefits of both MCS‐assisted and unassisted PCI compared with available surgical therapeutic options including surgical revascularization, durable LV assist device implantation, and heart transplantation. Appropriate patient selection is particularly critical in light of the potential for device‐related complications 44‐46 …”
Section: Preprocedural Assessment Of Coronary Anatomical Complexity Amentioning
confidence: 99%
“…Accordingly, HR‐PCI was defined as the presence of at least 1 of the following criteria: (1) medical comorbidities resulting in >1.1% estimated periprocedural mortality by the National Cardiovascular Data Registry CathPCI mortality model, (2) left ventricular ejection fraction ≤35%, or (3) VA synergy between percutaneous coronary intervention with taxus and cardiac surgery (SYNTAX) score ≥15, as previously published. 3 , 10 , 24 A multioperator procedure was defined as the participation of ≥2 attending operators. Patients undergoing PCI for cardiac arrest, ST‐segment–elevation myocardial infarction, or other emergent indications were excluded to focus the analysis on cases with a conscious, premeditated decision for multioperator intervention.…”
Section: Methodsmentioning
confidence: 99%
“…4 , 5 , 6 Advances in percutaneous coronary intervention (PCI) techniques and the advent of percutaneous mechanical circulatory support have provided new avenues to treat these challenging patients, at the price of increased procedural complexity and cost. 7 , 8 , 9 , 10 , 11 , 12 , 13 Although the overall morbidity and complexity of patients referred for percutaneous intervention has increased, there has been a concomitant decrease in PCI volumes, creating a challenge for today’s operators. PCI is becoming more and more complex to treat a sicker population, but there is less case volume to support the development of operators’ technical skills and experience.…”
mentioning
confidence: 99%
“…The STICH trial (Surgical Treatment for Ischemic Heart Failure) revealed fewer all-cause mortality, cardiovascular and heart failure hospitalizations in CABG with optimal medical therapy when compared with medical therapy alone [8,9]. The role of PCI in patients with heart failure has evolved tremendously during the past decade, given that the population undergoing this procedure is now older, with significantly greater comorbidities, and thus, at a higher risk for invasive surgical interventions [10]. This has resulted in the development of sophisticated techniques and numerous adjunct supportive therapies to provide hemodynamic support and reduce the risk of this procedure, often described as high-risk PCI (HR-PCI).…”
Section: Management Of Coronary Artery Disease In Heart Failurementioning
confidence: 99%